PENINGKATAN PRESTASI BELAJAR SISWA MELALUI MULTIMEDIA PADA MATA PELAJARAN SEJARAH KELAS 6 SD NEGERI 3 KECAMATAN SAMADUA KABUPATEN ACEH SELATAN - Romi Prima Ayuza (Prodi Teknologi Informasi UIN Ar-Raniry Bekerjasama dengan Pusat Penelitian dan Penerbitan LP2M Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
From the observations seen at the State Elementary School 3 Samadua so far, it is still dominantly using the shared learning model, not finding that improvisation renews learning with changes in time and the environment in which students find themselves. Teachers who teach theory still do not use teaching materials. In the transmission of learning, educators still use the method of teaching or delivering material orally. This research is a field research using action research in the classroom (RAC). Data collection is done through observation or observations and experiments. The results of the study show that PowerPoint material can increase the output of learning history for students in grade VI History of the State Elementary School Tiga Samadua. The average value of the class experienced a significant increase. When not given treatment, the mean value of 59 is 59, after treatment in the first cycle, the class average value is higher as 70.1, then it is higher again in cycle II as much as 78. And in the postgraduate level, it is higher as 90. The number of students who complete their studies also increased, initially at the time of completion of the pre-action there were 9 students or 20.3%, in the cycle, 60.3% at first, then increased. in the second cycle is 75.5%. And increased sharply at the postgraduate level to 87.3%.